Fast neuron studies: a proportional counter method of fast neutron spectroscopy - Reid, George C. (The University of Edinburgh, 1954)
he design, construction and calibration of a recoil- coincidence- absorption fast neutron spectro- meter has been described, and the theoretical resolving power of the instrument has been dis- cussed, in so far as it is determined by the geo- metry of the proportional counter telescope and by the finite thickness of the polythene film radiator. The geometrical resolution has been seen to be of the order of 2% of the energy of the incident neutrons, so that the absolute resolution, express- ed in units of energy, decreases with energy as the reciprocal of the neutron energy. At the same time, however, the energy spread introduced by the poly- thene film decreases as shown in Fig. 16. By com- bining the energy spreads from these two effects, we obtain a curve of the form shown in Fig. 24. Here the ordinate is the width at half- height of the line produced by monoenergetic neutrons whose energy is given by the abscissa. It can be seen that the theoretical resolution attains its best value (about 90 keV) in the neighbourhood of 3 MeV neutron energy, and is below 300 keV over the entire range of energy for which the instrument was designed.

While this resolution is not as good as that claimed for the photographic plate method, it is felt that the instrument is of great use in ob- taining rapid,yet quite accurate, surveys of fast neutron spectra, and can be used either for the determination of the positions of energy levels in light nuclei, or as an auxiliary instrument in other fast neutron work.

The neutron spectrum resulting from the bom- bardment of a thick target of beryllium by 750 keV deuterons has been examined at an angle of 00 to the deuteron beam, and the existence of an excited level in the product nucleus B10 at about 2.85 MeV has been verified.

Partial verification of the existence of a level in Be8 at 5.4 MeV has also been obtained by a survey of a section of the neutron spectrum from deuteron bombardment of lithium, while no evidenc has been found of a previously reported level at 4.9 MeV.